PENERAPAN MODEL INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS X SMAN 5 PONTIANAK - Astuty, Dwi Puji; Maria Silitonga, Haratua Tiur; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to improve the learning outcomes of class X students of SMA 5 Pontianak through inquiry learning using the experimental method. The form of research carried out in the form of a pre-experimental design with the design of one group pretest-posttest. This study involved 37 students of class X IPA 5 in SMA 5 Pontianak through a purposive sampling technique. The research instrument was made in the form of RPP, LKPD and description tests totaling 8 questions representing three indicators. The results of the study showed that there was an increase in student learning outcomes by 88.6%, from 34.84 to 65.76 is calculated from the average value of the pretest and posttest. Meanwhile, the results of effectiveness calculations using effect size show a significant difference of 1.85 with a high category. This shows that the application of the inquiry model is able to improve student learning outcomes in the measurement material so that the application of inquiry learning models is feasible to be considered as an alternative in an effort to improve student learning outcomes.Â Keywords: Inquiry Model, Learning Outcomes, Measurement.Â